Cryogenic Temperature Response Of Fibre Optic Long Period Gratings. - James, Stephen W.; Tatam, Ralph P.; Twin, Andrew; Bateman, Rod; Noonan, Paul (IOP Publishing, 2003)
The thermal response of the attenuation bands of an optical fibre long period grating was monitored over a temperature range of 4.2–280 K. A linear dependence of the central wavelength of the band, of gradient 0.2 nm K-1, was observed over the range 77–280 K. A measurable wavelength shift was observed at temperatures as low as 20 K.
Keywords: fibre optic sensor; fibre grating; long period grating; temperature; cryogenic